A review on methods and devices to determine body iron status - Azrina T.N.; Kar Y.B.; Feng L.W.; Sankar P.A.L.; Ammar A.N.; Al-Haiqi A.M.; Lai Mei I. (World Research Association, 2023)
Despite the importance of iron for human body, the lack of iron as well as excess iron will lead to various health issues. Iron deficiency is the most common nutritional deficiency in the world responsible for a staggering amount of ill health, lost productivity as well as premature death. Iron overload causes iron toxicity leading to organ dysfunction such as damage in liver, heart and central nervous system. Detecting iron status at early stage is of paramount important especially in poor countries that have limited access to sophisticated laboratory diagnosis. Real-time measurement is always a hurdle due to time consuming and costly equipment required. This review discusses the methods and devices used to determine the body iron status. It also explores the perspective for the development of low-cost body iron reader. 2018 Research Journal of BioTechnology. All rights reserved.